Features of Determining the Condition of the Thyroid Gland in Young People Residing in Regions with Partially Expressed Iodine Deficiency (Indian Journal of Public Health Research & Development, 2020)
Anthropometric and sonographic studies of 92 school children of younger and older age groups were carriedout. It has been proven that the transverse size of the thyroid gland is larger in boys than in girls in bothage groups. However, in a sonographic assessment of thyroid volume, opposite trends were obtained. Toassess thyromegaly, a sonographic assessment of thyroid volume is necessary, since the determination ofthe volume of the thyroid gland by ultrasound is deprived of the subjectivity inherent in different doctors onpalpation. However, an assessment of the size of the thyroid gland must be carried out in accordance withthe body (area) of the child, calculated on the basis of height and weight.
Keywords: Anthropometry, sonography, thyroid gland, students, prevention.